Development of a theory and evidence-based digital intervention tool for weight loss maintenance: The NoHoW Toolkit [preprint] - Marques, Marta (2020)
Background: Many weight loss programs show short-term effectiveness, but subsequent weight loss maintenance is difficult to achieve. Digital technologies offer promising means to delivering behaviour change approaches at low cost and on a wide scale. The NoHoW project was a European Commission H2020-funded project aimed to develop, test, and evaluate a digital Toolkit designed to promote successful long-term weight management. The Toolkit was tested in an 18-month large-scale international 2 x 2 factorial (motivation and self-regulation versus emotion regulation) randomised controlled trial, conducted in overweight/obese adults who lost ≥5% of their body weight in the preceding twelve months before enrolment into the intervention. Objective: This paper describes the development of the NoHoW Toolkit focusing on the logic models, content and specifications, and results from user testing. Methods: The Toolkit was developed using a systematic approach including (1) development of the theory-based logic models, (2) selection of behaviour change techniques, (3) translation of these techniques into a digital web-based app (NoHoW Toolkit components), (4) technical development, (5) user evaluation and refinement of the Toolkit. Results: The Toolkit included a set of web-based tools and inputs from digital tracking devices (smart scales and activity trackers), with modules targeting weight, physical activity, and dietary behaviours. The final Toolkit was comprised of 34 sessions, distributed through 15 modules, providing active content over a 4-month period. The motivation and self-regulation arm consisted of 8 modules (17 sessions), the emotion regulation arm was presented with 7 modules (17 sessions), and the combined arm received the full Toolkit (15 modules, 34 sessions). The sessions included a range of implementations, such as videos, testimonies, and questionnaires. Further, the Toolkit contained 5 specific data tiles for monitoring weight, steps, healthy eating, mood and sleep. Conclusions: A systematic approach to the development of digital solutions based on theory, evidence, and user testing, may significantly contribute to the advancement of the science of behaviour change and improve current solutions for sustained weight management. Testing the Toolkit using a 2x2 design provided a unique opportunity to examine the effect of motivation and self-regulation and emotion regulation separately, as well as the effect of their interaction in weight loss maintenance.